Caliothrips tongi sp.n. (Thysanoptera, Thripidae) from China, and a dubious record of North American Bean Thrips - Mound, Laurence A.; Zhang, Hongrui; Bei, Yawei (Zootaxa, 2011)
A new species, Caliothrips tongi, is described from eastern China, and an old record of the North American bean thrips, Caliothrips fasciatus (Pergande), from the same area is considered unreliable. Oneilliella pallidizonata Kudo is transferred to Caliothrips as a new combination.